Dealing with Campus Safety Issues - Nancy P. Kropf (Academic Chairpersons Conference Proceedings, 2017)
As an administrator, traumatic and unexpected events in a unit require a unit head to deal with the situation and related consequences. Using examples of events that have impacted safety of students and faculty, this presentation will highlight responses when dealing with harmful or threatening campus experiences.
Keywords: safety; traumatic events; harm; threats; violence